Peningkatan Kemampuan Menjadi MC Upacara Bendera 17 Agustus Pada Siswa SMAN 2 Kec. Siak Hulu - Amanan; Hermansyah; Juswandi (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2024)
The Master of Ceremony (MC) or Host is a figure who plays a central role in directing an event or activity with professionalism and skill in providing entertainment(Meifiliana, 2021). The presence of an MC is inseparable from various events, ranging from formal ones to sacred moments such as the 17th of August Ceremony. As the controller of the event's flow, the MC is responsible for ensuring that every aspect runs according to the schedule set either by themselves or by the event organizers. The MC also ensures that the message conveyed is well received by the audience (Meylina, 2022). This community service activity was held at SMA Negeri 2, Siak Hulu District, Kampar Regency. The purpose of this activity is to provide deep understanding, training, and practical experience for students to become competent and professional MCs in facing the 17th of August Ceremony. It is hoped that the results of this research will make a significant contribution to the development of students' knowledge and understanding regarding the role and skills of an MC, as well as open up broad career opportunities in the professional world in the future. Keywords: Improvement, Skills, Becoming an MC, Flag Ceremony.